Reducing COVID-19 Risk through Dietary Supplementation of Plant Mannose Binding Lectins - Kevin, K. Lau (International Journal of Coronaviruses, 2020)
Mannose binding lectins (MBL), a key molecule in our innate immune response, contributes to host defense against coronaviruses such as SARS-CoV. This article reviews the role of MBL in the innate immune response against coronavirus infections, highlights evidence of MBL’s significance, and suggests dietary MBL supplementation through increased consumption of fruits and vegetables as an accessible and viable approach to minimizing COVID-19 infection risk. Increasing consumption of plant lectins (e.g., eating fruits and vegetables) may reduce COVID-19 risks.
Keywords: SARS-CoV; SARS-CoV-2; Coronavirus; Mannose Binding Lectins; MBL; Lectins; Diet; Public Health